Nietzsche & philosophy - Deleuze, Gilles 1925-1995; Tomlinson, Hugh (New York Columbia University press, 1983)
Nietzsche and Philosophy has long been recognized as one of the most important accounts of Nietzsche's philosophy, acclaimed for its rare combination of scholarly rigour and imaginative interpretation. Yet this is more than a major work on Nietzsche: the book opened a whole new avenue in post-war thought. Here Deleuze shows how Nietzsche began a new way of thinking which breaks with the dialectic as a method and escapes the confines of philosophy itself.